A Desilylative Approach to Alkyl Substituted C(1)‐Ammonium Enolates: Application in Enantioselective [2+2] Cycloadditions. Issue 38 (8th August 2022) - Wang, Yihong; Young, Claire M.; Liu, Honglei; Hartley, Will C.; Wienhold, Max; Cordes, David. B.; Slawin, Alexandra M. Z.; Smith, Andrew D.
Abstract: The catalytic generation of C(1)‐ammonium enolates from the corresponding α‐silyl‐α‐alkyl substituted carboxylic acids using the isothiourea HyperBTM is reported. This desilylative approach grants access to α‐unsubstituted and α‐alkyl substituted C(1)‐ammonium enolates, which are typically difficult to access through traditional methods reliant upon deprotonation. The scope and limitations of this process is established in enantioselective [2+2]‐cycloaddition processes with perfluoroalkylketones (31 examples, up to 96 % yield and >99 : 1 er), as well as selective [2+2]‐cycloaddition with trifluoromethyl enones (4 examples, up to 75 % yield and >99 : 1 er). Preliminary mechanistic studies indicate this process proceeds through an initial kinetic resolution of an in situ prepared (±)‐α‐silyl‐α‐alkyl substituted anhydride, while the reaction process exhibits overall pseudo zero‐order kinetics. Abstract : The catalytic generation of unsubstituted and alkyl substituted C(1)‐ammonium enolates from α‐silyl‐α‐alkyl substituted carboxylic acids using the isothiourea HyperBTM has been developed and applied in enantioselective [2+2]‐cycloaddition reactions.